The Financial System in China: Determinants and Future - Teng, Xiaowen (2007)
The surprising growth rate of China's economy has been put important attention by the rest of the world. However, whether China's economy could keep on developing at such rate is pending. Since one country's economy cannot grow healthily and rapidly without the support of an appropriate financial system, it is very important to analyze the factors that affect China's financial system for the further development of its financial system, and thereby its economy.